Future Entrepreneurial Intentions in Chilean and Basque High School Students [Futuras Intenciones de Emprender en Estudiantes de Estudios Secundarios Chilenos y Vascos] - Torres-Ortega, J (CIRIEC, 2021)
Entrepreneurial initiatives –whether social or commercial– generate a significant economic and social impact. For this reason, supporting entrepreneurship and entrepreneurs has become a real necessity today, since the development and growth of our territories and countries depend to a large extent on it. In this context, achieving a deeper understanding of the main determinants of entrepreneurship is undoubtedly of great value for economies and society in general. This is particularly important in the case of adolescents, given the need to stimulate entrepreneurship from an early age. The present article aims to make a contribution in this sense, with the central objective of characterizing and comparing high school students from two different countries from the point of view of a series of personal and family characteristics, relating them to their future entrepreneurial intentions, whether in the field of commercial and/or social entrepreneurship. To achieve this objective, the same survey was applied to a sample of Chilean (n=4661) and Basque (n=5767) students. The results reveal that Chilean students exhibit a greater inclination to follow an entrepreneurial career than their Basque peers. Likewise, it is observed that a set of traits that shape an “entrepreneurial personality” are associated with higher future entrepreneurial intentions in both groups of students. Those who develop intentions of social entrepreneurship, on the other hand, are more closely linked to the possession of social sensitivity and a sense of ethics. © 2021. CIRIEC-Espana Revista de Economia Publica, Social y Cooperativa. All Rights Reserved.